Endovascular treatment of ruptured pancreaticoduodenal artery aneurysm: The importance of collateral vessels. A case report. (2017) - Ricci, Gabriele; Riu, Pascale; Attinà, Grazia Maria; Trombetta, Silvia; Ialongo, Pasquale; Di Cosimo, Carla; Mancuso, Rosaria; Marini, Pierluigi
Highlights: Ruptured pancreaticoduodenal artery aneursym is a very rare but potentially catastrophic occurence in an emergency department and its treatment is challenging. Very few cases of emergency endovascular treatment of ruptured visceral aneursyms are reported in the literature. This case report has the intention to elucidate in pancreaticodudoenal artery aneursym the importance of collateral vessels that could feed the aneurysm sac even after embolization of the inflow and outflow of the aneurysm. Abstract: Introduction: True pancreaticoduodenal artery aneurysm occurrence is infrequent, but it is a fatal disease and accounts for accounts for <2% of all visceral aneurysms. Presentation of case: A 62-year-old man with a two-day history of epigastric pain was admitted at emergency department. CT showed a retroperitoneal haematoma due to a 1.5 cm posterior inferior PDA ruptured aneurysm. Angiography had been conducted immediately: both inflow and outflow of the aneurysm were embolized. Another CT scan had been conducted, which revealed residual flow inside the aneurysm sac fed by small collateral vessels. Sub-selective catheterization was repeated and definitive haemostasis was obtained by embolizing the collateral vessels. Postoperative course was uneventful. CT scan follow-up at 36 months showed no abnormalities. Discussion: The incidence rate of pancreaticoduodenal artery aneurysm rupture has been estimated to be less than or equal to 65%. In the case of rupture the treatment is challenging and mortality had been reported up to 50%. Endovascular treatment showed superior results as compared to surgical treatment of aneurysms, especially in emergency settings. Conclusion: The authors elucidate the importance of occlusion of inflow and outflow of the aneurysm in conjunction with the occlusion of collateral vessels to avert reperfusion of the sac. Simultaneous handling of celiac axis stenosis is still prone to controversy: no relapse of aneurysm have been reported in patients with celiac axis stenosis at long-term follow-up, simultaneous treatment should be reserved when angiography is alarming for likely hepatic or duodenal ischemia.